Statistical estimates of hominin origination and extinction dates: A case study examining the Australopithecus anamensis–afarensis lineage. Issue 138 (January 2020) - Du, Andrew; Rowan, John; Wang, Steve C.; Wood, Bernard A.; Alemseged, Zeresenay
Abstract: Reliable estimates of when hominin taxa originated and went extinct are central to addressing many paleoanthropological questions, including those relating to macroevolutionary patterns. The timing of hominin temporal ranges can be used to test chronological predictions generated from phylogenetic hypotheses. For example, hypotheses of phyletic ancestor–descendant relationships, based on morphological data, predict no temporal range overlap between the two taxa. However, a fossil taxon's observed temporal range is almost certainly underestimated due to the incompleteness of both the fossil record itself and its sampling, and this decreases the likelihood of observing temporal overlap. Here, we focus on a well-known and widely accepted early hominin lineage, Australopithecus anamensis – afarensis, and place 95% confidence intervals (CIs) on its origination and extinction dates. We do so to assess whether its temporal range is consistent with it being a phyletic descendant of Ardipithecus ramidus and/or a direct ancestor to the earliest claimed representative of Homo (i.e., Ledi-Geraru). We find that the last appearance of Ar. ramidus falls within the origination CI of Au. anamensis – afarensis, whereas the claimed first appearance of Homo postdates the extinction CI. These results are consistent with Homo evolving from Au. anamensis – afarensis, but temporal overlap between Ar. ramidus and Au. anamensis – afarensis cannot be rejected at this time. Though additional samples are needed, future research should extend our initial analyses to incorporate the uncertainties surrounding the range endpoints of Ar. ramidus and earliest Homo . Overall, our findings demonstrate the need for quantifying the uncertainty surrounding the appearances and disappearances of hominin taxa in order to better understand the timing of evolutionary events in our clade's history.